Антропологічний доробок Ф. Вовка: сучасний погляд - Сегеда, С.П. (Археологія і давня історія України, 2012)
У статті подана загальна оцінка антропологічної концепції Ф. Вовка у світлі сучасних наукових даних. Статья посвящена анализу антропологического наследия Федора Вовка — выдающегося украинского ученого конца ХІХ — нач. ХХ ст., создавшего собственную этнологическую школу. Обосновывается вывод о том, что основные положения концепции антропологического состава украинского народа, разработанной Ф. Вовком в 1916 г., выдержали испытания временем. The paper is devoted to the analysis of the anthropological heritage of Fedir Vovk-the distinguished Ukrainian scientist of the end of the XIX- the beginning of the XX-th century., who created his own scientific school in ethnology. It is known that the main statements of the concept of the anthropological composition of the Ukrainian nation, developed by F.Vovk in 1916, were proved by time.